Phospholipase D1 is upregulated by vorinostat and confers resistance to vorinostat in glioblastoma. Issue 1 (1st September 2020) - Kang, Dong Woo; Hwang, Won Chan; Noh, Yu Na; Kang, Youra; Jang, Younghoon; Kim, Jung‐Ae; Min, Do Sik
Abstract: Glioblastoma (GBM) is an aggressive brain tumor and drug resistance remains a major barrier for therapeutics. Epigenetic alterations are implicated in GBM pathogenesis, and epigenetic modulators including histone deacetylase (HDAC) inhibitors are exploited as promising anticancer therapies. Here, we demonstrate that phospholipase D1 (PLD1) is a transcriptional target of HDAC inhibitors and confers resistance to HDAC inhibitor in GBM. Treatment of vorinostat upregulates PLD1 through PKCζ‐Sp1 axis. Vorinostat induces dynamic changes in the chromatin structure and transcriptional machinery associated with PLD1 promoter region. Cotreatment of vorinostat with PLD1 inhibitor further attenuates invasion, angiogenesis, colony‐forming capacity, and self‐renewal capacity, compared with those of either treatment. PLD1 inhibitor overcomes resistance to vorinostat in GBM cells intracranial GBM tumors. Our finding provides new insight into the role of PLD1 as a target of resistance to vorinostat, and PLD1 inhibitor might provide the basis for therapeutic combinations with improved efficacy of HDAC inhibitor. Abstract : Phospholipase D1 (PLD1) is a transcriptional target of histone deacetylase (HDAC) inhibitors and confers resistance to HDAC inhibitor in glioblastoma (GBM). Cotreatment of vorinostat with PLD1 inhibitor further attenuates invasion, angiogenesis, colony‐forming capacity, and self‐renewal capacity, compared with those of either treatment. PLD1 inhibitor overcomes resistance to vorinostat in GBM cells and intracranial GBM tumors.